Leveraging of remote sensing and GIS on mapping in urban and regional planning applications - Mohd. Noor, Norzailawati; Abdullah, Alias; Nuraulia, Rusni (Institute of Physics Publishing, 2014)
While remote sensing applications represent a major though still underused source of urban data, the proposed combination between remote sensing and Geo-information System (GIS) in urban and regional planning is not fully explored. In order to measure changes in land use, the need of platform in monitoring, recording, and predicting the changes is necessary for planners and developers. In advance technology of mapping process, remote sensing and GIS as tools for urban planning are already recognised. But, due to lack of implementation and awareness about the benefits of these tools, these terms look unusual. Therefore, this paper reviews the history of remote sensing and GIS in urban applications, technical skills and the challenges, and future development of remote sensing and GIS especially for urban development particularly in developing countries.